Analytical and Numerical Contact Stress Analysis of Spur Gears - Nestorovski, Blagoja; Simonovski, Petar (Science, Engineering and Technology, 2023)
The damage that occurs on the teeth flank of cylindrical gears is a complex phenomenon and depends on many factors. The most common cause for these damages is the high contact stress of the meshing gears. Although this contact pressure, by itself, cannot be a criterion for determining the durability of the gears, a good correlation has been found between the contact or Hertz pressure and the damage that occurs on the tooth flank. This paper analyzes the influence of the pressure angle α on the contact stress. Analytical calculation according to the ISO 6336-2:2006 and finite element method (FEM) was used for the analysis. Four cases were analyzed with a change in the pressure angle, i.e., cylindrical spur gears and pressure angles of 17.5°, 20°, 22.5° and 25°. In the results, it was noted that by increasing the pressure angle, the contact stress decreases. It can also be concluded that by increasing the pressure angle, the difference in the results between the analytical and FEM analysis, also increases.